The Validity of Standard Clauses in E-Commerce: The US Experience and Suggestions for Vietnam - Thu Phuong, Tran Thi (VNU Journal of Science: Legal Studies; Vol 40 No 2DO - 10.25073/2588-1167/vnuls.4578, 2024)
Consumers tend to participate more and more in e-commerce transactions. When participating in these transactions, in many cases, consumers will sign and implement standard terms. The validity of the standard clauses is always an issue of interest to researchers, especially when they contain provisions on governing law and jurisdiction. So, how is the legal effect of these provisions determined in practice? Using the comparative method and the approach to typical cases resolved by US law, this article focuses on the above-mentioned issues but is limited to the content related to the contracting process without commenting on the clauses. As a result, the article proposes solutions for improving Vietnamese law.